Gaseous and heterogeneous detonations : science to applications - Roy, Gabriel D., editor; Frolov, Sergei M., editor; Kailasanath, Kazhikathra, editor; Smirnov, Nickolay N., editor ([Moscow] : ENAS Publishers, 1999)
Includes bibliographical references